Digital Economic Education and MSME Assistance Project Bamboo to Improve the Quality and Quantity of Bamboo Products in Pendem Village, Mojogedang District - sasmini, sasmini; kurniawan, diki; Ramdhani, Arba Nur Wahyu; Ristanto, Rohmad Angga; Sulistyawati, Nurul; Setyowati, Yuliana Dyah; Oktavia, Nindia Dila; Ferdianyta, Medianasari; Putri, Regita Cahyani (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article explores the implementation of digital economy education and mentoring for Project Bamboo's Micro, Small and Medium Enterprises (MSMEs) to improve product quality and quantity located in Pendem Village, Mojogedang District, Karanganyar Regency. This research assessed the impact of the digital platform and mentoring on product improvement, business efficiency, and market competitiveness. Findings showed improvements in product quality and quantity attributed to digital technology and customized mentoring. In addition, the research identified challenges and opportunities encountered during the implementation process. The insights gained from this research contribute to a better understanding of the gained from this research contribute to a better understanding of the utilization of digitalization and mentoring to empower MSMEs and foster sustainable economic development in rural communities.